Spacial analysis of foreclosure and neighborhood characteristics in Miami metropolitan area, Florida - Ogbe, Adejoh Emmanuel (2015)
In 2013, the State of Florida had 13 of the top 20 metropolitan statistical areas (MSA) with the highest foreclosure rate in the country. Despite the high ranking, extensive research on foreclosure has yet to be carried out within the Miami-Fort LauderdalePompano Beach MSA. This research is a foray into an uncharted territory to understand the relationship between foreclosure and neighborhood characteristics in the Miami metropolitan area (MMA) within Miami-Dade County. The study was conducted in two phases: The first phase was to identify the foreclosure pattern in the MMA from 2010- 2013 by implementing the use of spatial analysis such as nearest neighbor analysis, spatial autocorrelation, and cluster and outlier analysis. The statistical analysis used also included correlation analysis, principal component analysis, and regression analysis. The dataset used contained foreclosure count from 2010-2013 and the 2010 census tract level data on neighborhood characteristics such as ethnicity and racial compositions, socioeconomic, demographic, and housing. The spatial and statistical analysis carried out was used to identify the relationship between foreclosure and the neighborhood characteristics. The second phase studied the effect of foreclosure on crime in the city of Miami. Crime data from 2011-2012 was used to study the relationship between crime, foreclosure, and the above mentioned neighborhood characteristics. The statistical analysis carried out in this phase included correlation analysis and regression analysis. Results of the study showed that in MMA, the relationship between foreclosure and other neighborhood characteristics was insignificant. However, the result for the spatial pattern of foreclosure in MMA showed that houses of similar market values were clustered in the northeastern, southeastern and central areas. Additionally, areas dominated by the African American population showed low economic activity and high foreclosure concentration compared to other areas, which could be an influence of subprime lending. Finally, foreclosure alone had no impact on crime whatsoever, but vacancy rate was statistically significant to property crime in the city of Miami. These findings are important in understanding foreclosure distribution and clustering patterns in MM